Squid-Derived Chitin Oligosaccharides Are a Chemotactic Signal during Colonization by Vibrio fischeri - Mandel, Mark J. (American Society for Microbiology, 2012)
Chitin, a polymer of N-acetylglucosamine (GlcNAc), is noted as the second most abundant biopolymer in nature. Chitin serves many functions for marine bacteria in the family Vibrionaceae (“vibrios”), in some instances providing a physical attachment site, inducing natural genetic competence, and serving as an attractant for chemotaxis. The marine luminous bacterium Vibrio fischeri is the specific symbiont in the light-emitting organ of the Hawaiian bobtail squid, Euprymna scolopes. The bacterium provides the squid with luminescence that the animal uses in an antipredatory defense, while the squid supports the symbiont's nutritional requirements. V. fischeri cells are harvested from seawater during each host generation, and V. fischeri is the only species that can complete this process in nature. Furthermore, chitin is located in squid hemocytes and plays a nutritional role in the symbiosis. We demonstrate here that chitin oligosaccharides produced by the squid host serve as a chemotactic signal for colonizing bacteria. V. fischeri uses the gradient of host chitin to enter the squid light organ duct and colonize the animal. We provide evidence that chitin serves a novel function in an animal-bacterial mutualism, as an animal-produced bacterium-attracting synomone.